Exploring the role of community radio programming in youth empowerment: A case study of Sajonisi Youth Radio (SYR) in the Eastern Cape, South Africa - Pinyana, Ndlelantle (Stellenbosch : Stellenbosch University, 2024)
Thesis (MA)--Stellenbosch University, 2024.